Dorothy Day and Gender Identity: The Rhetoric and the Reality - O'Connor, June (Horizons, 1988)
Dorothy Day's sense of herself as a woman and as a mother feature prominently in her writings. In light of recent inquiries into gender identity and gender ideology, and given Dorothy Day's prominence as editor, social activist, anarchist, pacifist, and religious author, questions about her views regarding woman's role and related feminist concerns invite investigation. The paper argues that although Dorothy Day did not become a vocal advocate nor public ally of the women's movements in twentieth-century American life because of some fundamental differences in viewpoint and loyalty, she did share a number of affinities with feminist perspectives. To investigate her thought on this topic enables us to understand Dorothy Day more fully and to bring a critical eye to selected features of feminism, discerning (from Day's standpoint) both strengths and weaknesses.